Transitional living spaces to improve the quality of life of marine fishermen in Kuantan - Mazyoona, Aminath; Mohd Zairul (Human Resources Management Academic Research Society (HRMARS), 2024)
Transitional living spaces are considered short-term accommodation arrangements designed to help individuals or families experiencing a period of transition or instability. They are expected to lead them towards a more stable setting of living conditions. However, the current architectural approach towards transitional living spaces or accommodations for fishermen in Malaysia does not address the needs of fishermen properly and is usually designed universally. Therefore, due to the improper spatial quality of such living spaces, instead of improving the living quality of the fishermen, it has become a bigger challenge to overcome. This research aims to explore the living conditions of fishing communities in Malaysia and produce a design framework for them to design transitional living spaces. This research is based on ethnography of qualitative methodology and will use literature review, interview, and observation as data collection methods. Furthermore, the expected outcome is to produce a design framework for suitable transitional living spaces for fishermen in Kuantan. Producing such a framework will help increase awareness of the importance of transitional living spaces for fishermen, improving the quality of fishermen’s livelihood. This research will only focus on producing a framework for transit living spaces for middle-aged fishermen.